Chloromethyl-modified Ru(ii) complexes enabling large pH jumps at low concentrations through photoinduced hydrolysis. Issue 43 (24th October 2019) - Tian, Na; Sun, Weize; Feng, Yang; Guo, Xusheng; Lu, Jian; Li, Chao; Hou, Yuanjun; Wang, Xuesong; Zhou, Qianxiong
Abstract : Photo-induced hydrolysis of benzyl chlorides was first utilized to fabricate PAGs with high photoacid quantum yields and large photoacid capacities. Abstract : Photoacid generators (PAGs) are finding increasing applications in spatial and temporal modulation of biological events in vitro and in vivo . In these applications, large pH jumps at low PAG concentrations are of great importance to achieve maximal expected manipulation but minimal unwanted interference. To this end, both high photoacid quantum yield and capacity are essential, where the capacity refers to the proton number that a PAG molecule can release. Up to now, most PAGs only produce one proton for each molecule. In this work, the hydrolysis reaction of benzyl chlorides was successfully leveraged to develop a novel type of PAG. Upon visible light irradiation, Ru(ii ) polypyridyl complexes modified with chloromethyl groups can undergo full hydrolysis with photoacid quantum yield as high as 0.6. Depending on the number of the chloromethyl groups, the examined Ru(ii ) complexes can release multiple protons per molecule, leading to large pH jumps at very low PAG concentrations, a feature particularly favorable for bio-related applications.